Acceptability of ice cream products of red fruit (Pandanus conoideus lamk) with sago flour subtitution (Metroxylon sagu rottb) - Radeny Ramdany; La Supu; Fatimah Nurlathifach Pulukadang (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Ice cream is a frozen food product that is processed through a combination of freezing processes in a mixture of various ingredients consisting of milk or milk products, sweeteners, emulsifiers, stabilizers, and flavor enhancers. The addition of ice cream with local Papuan food modifications, namely red fruit and sago flour, is expected to add nutrition and become a new innovation for local ice cream products in the City of Sorong, West Papua. The purpose of this study was to determine the acceptability of the red fruit ice cream product with sago flour substitution. The research design used was experimental research. The samples used as objects were ice cream products with the addition of red fruit juice and sago flour with 3 variations (S00, S20, S30). This study used a fairly trained panel of 25 people. The independent variable is the variety of ice cream with red fruit juice and sago flour substitution and the dependent variable is acceptance (taste, aroma, color, texture). The instrument used in this study was the hedonic test form. Acceptability analysis using the Friedman Test. The results showed that there were significant differences in taste (p-value 0.006), aroma (p-value 0.006), color (p-value 0.001), and texture (p-value 0.010) of ice cream products with the addition of red fruit juice and Sago flour. This study found that there were differences in the acceptance of ice cream with variations in the substitution of sago flour and red fruit.